Le Canada et le développement du droit international : La contribution de l’Affaire de la fonderie de Trail à la formation du nouveau droit de la pollution atmosphérique transfrontière. - Fitzgerald, Gerald (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1980)
The purpose of this article is to indicate how the decisions of the Trail Smelter Arbitral Tribunal, rendered in 1938 and 1941, have made a contribution to the development of international law, including, in particular, the emerging international legal rules relating to transboundary air pollution. Of particular importance was the Tribunal's enunciation of the principle of the international liability of a pollution-source state. The influence of the Trail Smelter case is examined in the light of the Corfu ChannelCase, the Nuclear Test Ban Treaty (1963), the Helsinki Rules (1966), the Stockholm Principles (1972), the Nuclear Test Cases (1973-74), the OECD Principles concerning Transfrontier Pollution (1974 and 1976), and the Joint Statement on Transboundary Air Quality by Canada and the United States (1979).Two of the most difficult problems for solution in the case of transboundary pollution are: (1) equal access and non-discrimination with respect to remedies, and (2) liability and compensation. Canadian law has certain gaps in this regard. These and other problems of transboundary pollution pose a challenge for the 1980s and the TrailSmelter principle could make a contribution to their solution.